1933
DOI: 10.1113/jphysiol.1933.sp003024
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of inorganic phosphate into and out of the skeletal muscles and bones of the frog

Abstract: IF a skeletal muscle from a frog is immersed in a Ringer's solution containing urea, the urea distributes itself between the muscle and the solution in such a manner as to indicate that the whole of the water of the muscle is available to dissolve urea . Recently it has been found that the same statement is true for the amino acid histidine [Eggleton and Eggleton, 1933], but the behaviour of the dipeptide carnosine in similar experiments indicated that only part of the water of the muscle was available to carn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1935
1935
1961
1961

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Lactate-Ringer of required strength was prepared by replacing an equivalent amount of sodium chloride in the Ringer by sodium lactate. The pH of the solution used was 7 1, but it was not thought necessary to buffer the Ringer as it was found that for small quantities of Ringer used in the experiments (1-1k times the weight of muscle), the final pH of Ringer was always about 7 4, and this is in agreement with the observation of M. G. Eggleton [1933], who found that the pH of Ringer fluid is ultimately about 7-4 for resting muscles whether the initial pH was 7-1 or 8-0.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…Lactate-Ringer of required strength was prepared by replacing an equivalent amount of sodium chloride in the Ringer by sodium lactate. The pH of the solution used was 7 1, but it was not thought necessary to buffer the Ringer as it was found that for small quantities of Ringer used in the experiments (1-1k times the weight of muscle), the final pH of Ringer was always about 7 4, and this is in agreement with the observation of M. G. Eggleton [1933], who found that the pH of Ringer fluid is ultimately about 7-4 for resting muscles whether the initial pH was 7-1 or 8-0.…”
supporting
confidence: 82%
“…Chloride, on the other hand, is present only in the "interspaces " and none is found in the "cells " (private communication from Dr. P. Eggleton). Inorganic phosphate [M. G. Eggleton, 1933] and lactate are present in both these fractions of muscle water, but under the conditions of the experiment there appears to be no exchange of these ions between the two fractions. But in all these cases it is found that the "interspace" water constitutes about one-third of the total muscle water.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…These figures are corroborated by recent analyses of dog muscle made by Hastings (24). Eggleton (25,26) has shown that certain solutes diffuse through all the water of the frog muscle, while other substances diffuse through only 20 to 30 per cent of the water of vital frog muscle, presumably the extracellular portion. After rigor mortis has set in this selective permeability disappears.…”
Section: Introductionmentioning
confidence: 99%